Analgesic, Anti-Inflammatory, and Antioxidant Activities of Byrsonima duckeana W. R. Anderson (Malpighiaceae) - Maria Christina dos Santos Verdam; Fernanda Guilhon-Simplicio; Kleyton Cardoso de Andrade; Karina Lorena Meira Fernandes; Tallita Marques Machado; Felipe Moura Araújo da Silva; Mayane Pereira de Souza; Hector Henrique Ferreira Koolen; Cristiane da Silva Paula; Beatriz Cristina Konopatzki Hirota; Vinícius Bednarczuk de Oliveira; Cristina Mayumi Sasaki Miyazaki; et al. (The Scientific World Journal)
Background. Byrsonima is a promising neotropical genus, rich in flavonoids and triterpenes, with several proven pharmacological properties. Nevertheless, Byrsonima duckeana W. R. Anderson is an Amazonian species almost not studied. Objective. To assess the antioxidant, anti-inflammatory, and analgesic activities of Byrsonima duckeana leaves. Materials and Methods. We analyzed an ethanol extract and its fractions for polyphenol content and UHPLC-MS/MS, phosphomolybdenum, DPPH, TBARS antioxidant tests, formalin-induced pain, carrageenan-induced peritonitis, acetic acid-induced abdominal writhings, and hot plate assays. Results. All the samples showed high polyphenol content and antioxidant capacity in the phosphomolybdenum, DPPH, and TBARS tests. We identified ethyl gallate, quinic acid, gallic acid, catechin, epicatechin, quercetrin, and quercetin in the samples. B. duckeana was able to reduce leukocyte migration in the carrageenan-induced peritonitis by 43% and the licking time in the formalin test by 57%. In the acetic acid-induced writhing test, the chloroform (FCL) and ethyl acetate (FEA) fractions were the most active samples. FEA was selected for the hot plate test, where all the dosages tested (5, 50, and 200 mg·kg−1) showed significant analgesic activity. Conclusion. B. duckeana has interesting analgesic and antioxidant activities, due to its high phenolic content, especially phenolic acids.